Opportunities for Audience Content Creation and Sharing on Popular Lithuanian Online News Sites - Stonkienė, Marija; Šupa, Maryja; Janiūnienė, Erika (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] Innovations such as content management systems, social networking, and mobile applications create technical possibilities for members of the audience to participate in the creation and sharing of media content. However, the extent of these changes differs across different cultural contexts, media outlets, and social groups within audiences, and more research is needed to explain whether or not the power balance between media outlets and audiences is shifting. This paper presents the results of an inquiry about audience participation in contemporary Lithuanian mass media. Three online news websites (Delfi.lt, 15min.lt and Lrytas.lt) were chosen because they cover the biggest audiences in terms of users reached. Data was collected via structural analysis of the websites to determine what technical means are provided for the users to interact with the media outlet, and qualitative interviews with editors representing each website were conducted to discuss institutional practices and policies related to audience participation. The findings show that in Lithuanian online mass media, audience participation in the creation and sharing of media content is limited. While some technological means are incorporated into the news websites (e.g., forms for sending articles or visual material to journalists, comment forms and social media sharing buttons), most of them are based on the institutional strategy of the audience as a resource, scoured for information or activities in a highly monitored and controlled environment. So far, there are few signs of the alternative institutional strategy of mass media as a platform for independent and motivated audience participation.